ENHANCED BLOOD PRESSURE VARIABILTIY IN A HIGH CARDIOVASCULAR RISK GROUP OF AFRICAN AMERICANS - Veerabhadrappa, Praveen (2010)
BACKGROUND: High blood pressure (BP) levels in African Americans elicit vascular inflammation resulting in vascular remodeling. BP variability (BPV) correlates with target organ damage. We aimed to investigate the relationship between inflammatory markers and BPV in African Americans. METHODOLOGY: 36 African Americans underwent 24-hr ambulatory BP monitoring (ABPM). BPV was calculated using the average real variability (ARV) index. Fasting blood samples were assayed for high sensitivity C-reactive protein (hs-CRP), tumor necrosis factor-alpha (TNF-α) and white blood cell (WBC) count. RESULTS: Significant association between hs-CRP and 24-hr systolic variability (r = 0.50; p = 0.012) and awake systolic variability (r = 0.45; p =0.02) was identified after adjusting for age, BMI and 24-hr mean BP. ABPM variables were compared between the hs-CRP tertile groups. In Post-hoc analysis, there was a significant difference in 24-hr and awake periods for both systolic and diastolic variability among the groups. TNF-α and WBC count showed no associations with ABPM variables. CONCLUSION: hs-CRP is associated with systolic variability and higher levels of hs-CRP are related with greater BPV. Higher inflammatory status influences wider fluctuations in systolic BP which in turn could facilitate early progression to target organ damage independent of absolute BP levelsin African Americans.